Wireless Subnanosecond RF Synchronization for Distributed Ultrawideband Software-Defined Radar Networks - Prager, Samuel; Haynes, Mark S.; Moghaddam, Mahta (IEEE transactions on microwave theory and techniques, 2020)
In this article, we present a distributed and decentralized synchronization algorithm for wireless sensor networks (WSNs). The proposed method achieves subnanosecond synchronization using low-cost commercial-off-the-shelf (COTS) Universal Software Radio Peripheral (USRP) software-defined radios (SDRs) and is implemented entirely in software without the need for custom hardware or atomic clocks. In an N sensor network, the proposed protocol results in each sensor having full knowledge of baseband clock offsets, RF carrier phase offsets, and pairwise RF time of flight to subnanosecond precision for the entire network after 2N total transmissions, making this method efficiently extendible to larger sensor networks. The method is decentralized and does not rely on a hierarchical master-slave structure, making it robust to sensor dropout in contested or harsh environments. The proposed methodology is validated in simulation and tested in field experiments using a three-sensor network. This work has a wide range of applications, including transmit (TX) beamforming, distributed sensor localization, and coherent multistatic/multiple-input-multiple-output (MIMO) radar imaging for autonomous sensor swarms.